Evaluación de modelos matemáticos aplicables al proceso de secado de los granos de cacao en un secador accionado por un módulo de inducción - Pauzhi Jiménez, Anderson Miguel (2025)
In this degree work, a mathematical modeling applicable to the cocoa drying process was carried out, with the purpose of finding the best mathematical model that describes and adjusts to the kinetics of bean drying, for which use was made of a total of thirty equations obtained from bibliographic sources, all of them were applied to the ten days of drying needed to complete the drying of the grain, the determination of the best fit was made from the results of the coefficients of determination (R2) closest to one and the root mean square errors (RSME) farthest from one. The general objective is to obtain a mathematical model that best fits the drying of cocoa with the use of an induction dryer, for which it was necessary to perform two drying experiments using Arduino Uno programming connected to three DS18B20 temperature sensors, the experimental data obtained were time, humidity and temperature in real time, performing with these variables the mathematical modeling in the application Curve Fitting Toolbox of Matlab®, the second phase of drying was performed for the validation of the mathematical model. The mathematical model that presented the best adjustment to cocoa drying was the Two-term Model, with a coefficient of determination of 0.9981 and a mean square error of 0.0084. Keywords: Mathematical modelling, coefficient of determination, root mean squared deviation.